2022
DOI: 10.3389/fonc.2022.812159
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Validation of Pre-Therapy Cervical Vertebrae Muscle Quantification as a Prognostic Marker of Sarcopenia in Patients With Head and Neck Cancer

Abstract: BackgroundSarcopenia is prognostic for survival in patients with head and neck cancer (HNC). However, identification of this high-risk feature remains challenging without computed tomography (CT) imaging of the abdomen or thorax. Herein, we establish sarcopenia thresholds at the C3 level and determine if C3 sarcopenia is associated with survival in patients with HNC.MethodsThis retrospective cohort study was conducted in consecutive patients with a squamous cell carcinoma of the head and neck with cross-sectio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 47 publications
3
16
0
Order By: Relevance
“…These results are consistent with recent literature by Olson et al. ( 16 ) which emphasized that sarcopenia was associated with poor survival outcomes in males but not in females. Our results suggest that our automated methods are dependable for use in prognostic outcome prediction.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are consistent with recent literature by Olson et al. ( 16 ) which emphasized that sarcopenia was associated with poor survival outcomes in males but not in females. Our results suggest that our automated methods are dependable for use in prognostic outcome prediction.…”
Section: Discussionsupporting
confidence: 93%
“…However, abdominal imaging is not available for all HNC patients. Importantly, Swartz et al (15), van Rijn-Dekker et al (6), and Olson et al (16) have recently suggested the C3 cervical vertebra musculature cross-sectional area may also be used to quantify sarcopenia accurately.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The segmentations provided in this data descriptor have been utilized as ground-truth segmentations in a previous study by Naser et al . 12 which yielded sarcopenia determination results (normal vs. depleted skeletal muscle) that were consistent with existing literature 9 , i.e., overall survival stratification is significant in males but not females as determined by Kaplan Meier analysis. Note: 4 patients included in the current data descriptor were excluded from the aforementioned analysis (TCIA ID’s: 0226, 0280, 0577, and 0607), due to oblique image orientation mask issues previously described in Methods.…”
Section: Technical Validationsupporting
confidence: 82%
“…Moreover, to date, there are no existing open-source repositories for body composition analysis data based on head and neck region imaging. Increasing evidence has shown the potential utility of sarcopenia determination using skeletal muscle in the head and neck region 2 , 9 . This is driven by the fact that many patients with HNC may not have abdominal imaging acquired as part of the standard workup, but will almost certainly have head and neck region imaging acquired, particularly due to its necessity for radiotherapy treatment planning 10 and staging purposes 11 .…”
Section: Background and Summarymentioning
confidence: 99%